HUBUNGAN KEINTIMAN SUAMI ISTRI DENGAN POSTPARTUM BLUES PADA WANITA POSTPARTUM DI HUNIAN TETAP KECAMATAN CANGKRINGAN DAERAH PASCA BENCANA ERUPSI MERAPI - , SUCI NUGRAHENI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Background: Mount Merapi eruption that occured in 2010 was a traumatic incident. Most people affected by the eruption relocated to permanent shelter. Staying in permanent shelter create new stressors for postpartum mother, one of which reduced the marital intimacy. This happens because of privacy between couples become distracted, lack of time with the couple, the absence of a husbandâs attention to the postpartum mother and frequent marital conflict. This psychosocial stressors is one of the factors that influence the occurrence of postpartum blues. Objective: The purpose of this study was to determine relationship between the marital intimacy and postpartum blues in postpartum women in permanent shelter Cangkringan District post Merapi eruption disaster area. Method: The study was non experimental with cross sectional design. The study was conducted in February â April 2014. The collection of data by administering questionnaires revised marital intimacy scale and EPDS with a sample 35 respondents were taken with a total sampling technique. Data were analyzed using chi-square test. Result: The result of this study showed that postpartum blues experienced by postpartum women in permanent shelter Cangkringan District were 60%. There were 65,7% postpartum women in permanent shelter Cangkringan District that have lack of marital intimacy. There was significant association between marital intimacy and postpartum blues with p= 0,02 (p<0,05). Conclusion: There was association between marital intimacy and postpartum blues in postpartum women in permanent shelter Cangkringan District post Merapi eruption disaster area.